1999
DOI: 10.1111/j.1469-7793.1999.769ad.x
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic effects of muscarine on ACh release at the frog neuromuscular junction

Abstract: 1. Presynaptic effects of muscarine on neurotransmitter release were studied at the frog neuromuscular junction, using focal depolarization of the presynaptic terminal to different levels. 2. Muscarine (10 ìÒ) had a dual effect on ACh release: concomitant inhibition and enhancement of release at the same patch of presynaptic membrane. 3. These two effects were maximal at low depolarizing pulses and diminished as depolarization increased. 4. At low depolarizing pulses, atropine (1 ìÒ) enhanced release, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
126
3
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(143 citation statements)
references
References 39 publications
12
126
3
2
Order By: Relevance
“…Figure 5A shows that the partial (selective M 1 receptor block with pirenzepine or M 2 block with methoctramine) or total (atropine) block of the mAChR mechanism, the function of which is to modulate ACh release (Slutsky et al, 1999;Minic et al, 2002;Santafé et al, 2003Santafé et al, , 2006, prevents exogenous BDNF from carrying out the potentiating action (BDNF produces a change no higher than ϳ10%; p Ͼ 0.05). These data indicate the importance of the link between the ACh-mAChR pathway and the BDNFtrkB intracellular pathway.…”
Section: Endogenous Bdnf and Nt-4mentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5A shows that the partial (selective M 1 receptor block with pirenzepine or M 2 block with methoctramine) or total (atropine) block of the mAChR mechanism, the function of which is to modulate ACh release (Slutsky et al, 1999;Minic et al, 2002;Santafé et al, 2003Santafé et al, , 2006, prevents exogenous BDNF from carrying out the potentiating action (BDNF produces a change no higher than ϳ10%; p Ͼ 0.05). These data indicate the importance of the link between the ACh-mAChR pathway and the BDNFtrkB intracellular pathway.…”
Section: Endogenous Bdnf and Nt-4mentioning
confidence: 99%
“…Link between the trkB and muscarinic pathways Several developmentally regulated mAChR subtypes are known to be linked to ACh release at presynaptic sites at the NMJ (Slutsky et al, 1999;Minic et al, 2002;Santafé et al, 2006Santafé et al, , 2007. Although the precise cellular localization of the subtypes has not been fully resolved because of the low specificity of the staining antibodies (Pradidarcheep et al, 2008;Wright et al, 2009), pharmacological and electrophysiological experiments show that M 1 (pirenzepine-sensitive) and M 2 (methoctramine-sensitive) subtypes of mAChRs are involved in the enhancement and inhibition of ACh release, respectively, in the adult.…”
Section: Endogenous Bdnf and Nt-4mentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this suggested mechanism was supported experimentally (3)(4)(5)(6)(7)(8) by using mainly the cholinergic neuromuscular junction (NMJ), where the M 2 muscarinic autoreceptor (M 2 R) controls both slow feedback inhibition (9,10) and fast ACh release (6)(7)(8). However, the relevance of this hypothesis for other NTs was not investigated.…”
mentioning
confidence: 99%
“…Accordingly, under physiological conditions of DIR, Ca 2ϩ is indeed necessary but membrane potential plays the pivotal role in release (5). In particular, we proposed that presynaptic inhibitory autoreceptors, in addition to their known role in feedback inhibition (6), are also the vehicle by which membrane potential controls initiation and termination of release. As a molecular mechanism for the calcium-voltage hypothesis we suggested that under rest conditions the release machinery is subject to a tonic block, which is attained by the association of the ligand-occupied inhibitory autoreceptor (which mediates feedback inhibition of transmitter release) with proteins of the exocytotic machinery.…”
mentioning
confidence: 99%